Old Journalism behind the Curtain. About Reporters - Teodorașcu, Fănel (Acta Universitatis Danubius. Communicatio, 2023)
When the Romanians finally had their “national newspapers”, most of these were not “information newspapers”, but “political newspapers”. After a while, “information” became dominant within the pages of the Romanian newspapers. Those who understood how much “waste of passion” used the “anonymous work of a reporter” to imply, a reporter that would substantially contribute to the success of a certain newspaper, were very few. Frequently, the reporter was forced to invent “clever strategies” in order to obtain the information which the readers would expect from him. Many people held the opinion that reporter, as a “second class journalist”, needed no head, but good legs, so as to complete his work (and do his job). In our study, we aim at analysing what the Romanian interwar press wrote about the reporter. In order to achieve this goal, we read many articles published in various newspapers and magazines.